A descriptive study of first time outpatient public psychiatric care after 65 years - Luc Daucé-Fleuret; Astrid Reilhac; Nathalie Alleton; Dominique Somme; Gabriel Robert (BMC, 2024)
Abstract Background Mental health in the older adults represents a public health issue, especially depression and suicide, and even more in the Brittany French region. Community Mental Health Centers (CMHC) are the front-line French psychiatric healthcare organizations, but the number, characteristics and trajectories of the older adults consulting there for the first time are unknown. Method An exhaustive cross-sectional study from medical records about first-time consultants in any CMHC of the Guillaume Régnier Hospital Center in 2019, and quantifying and describing the 65 and over ones according to socio-demographic, clinical, geographic and trajectory criteria. Results This population represents 9.7% of all first consulting in CMHCs. We can note that 70.5% are female, 46.8% are living alone and 31.2% are widowed. These 3 rates are higher than in the general population. The main diagnosis we found is mood disorder (35.1%). Organic mental disorders are scarce (8.2%). Most people are referred by a general practitioner (53.4%) or a specialist/hospital center (23.7%). The main referral at the end is to CMHC care (73.6%). Only 20.0% had a referral to non-psychiatric health professionals (GP, coordination support teams, geriatrics, other professionals). Significant differences in the referral at the end exist between 65 and 74, who are more referred to CMHC professionals, and 75 and over, who are more frequently referred to non-psychiatric health professionals. Significant discrepancies about who referred are found according to community area-type. Conclusion These results align with the literature about known health-related characteristics and the importance of depression in the older people. They question the link with non-psychiatric professionals, and the need to structure a homogeneous care organization in psychiatric care for the older adults with trained professionals, especially for the 75 and over.